The impact of corporate social responsibility on firm reputation and organizational citizenship behavior: The mediation of organic organizational cultures - Ali, Hussain; Yin, Jianhua; Manzoor, Faiza; An, Mengmeng (Frontiers in Psychology, 2023)
This study investigates the impact of corporate social responsibility (CSR) on firm reputation and organizational citizenship behavior, along with the mediating inclusion of organic organizational cultures (Clan and Adhocracy) in the medium and large enterprises of Pakistan. To do the path analysis and to investigate the mediating role of organic organization culture, Smart PLS was used. For data collection, the convenience sampling technique was used and responses from 360 questionnaires were the main data source. The results displayed that CSR has a significant and optimistic effect on a firm reputation and employees’ organizational citizenship behavior (OCB). Secondly, the outcomes showed a positive and full mediation effect of organic organizational cultures between CSR and firm reputation but a partial mediation effect of organic organizational cultures between CSR and employees OCB. Further, the results demonstrated a positive and significant influence of employees’ OCB on a firm reputation. The extensive analysis of all factors of the study was autonomously examined to identify the insights that verify how the inclusion of organic organizational cultures can boost the firm reputation and employees’ OCB. Theoretical implications and future research direction are discussed.